2014
DOI: 10.1111/ejss.12165
|View full text |Cite
|
Sign up to set email alerts
|

Improving the prediction performance of a large tropical vis‐NIR spectroscopic soil library from Brazil by clustering into smaller subsets or use of data mining calibration techniques

Abstract: Effective agricultural planning requires basic soil information. In recent decades visible near-infrared diffuse reflectance spectroscopy (vis-NIR) has been shown to be a viable alternative for rapidly analysing soil properties. We studied 7172 samples of seven different soil types collected from several regions of Brazil and varying in organic matter (OM) (0.2-10.3%) and clay content (0.2-99.0%). The aim was to explore the possibility of enhancing the performance of vis-NIR data in predicting organic matter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
57
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(72 citation statements)
references
References 33 publications
9
57
0
1
Order By: Relevance
“…It is clear that VIS-NIR-SWIR spectra contain useful information that can be used to derive estimates of soil properties. For example, absorption features in the VIS-NIR wavelength (400-1000 nm) are characteristics of the presence of soil carbon and iron oxide [34,35,[48][49][50], and those in the SWIR (1000-2500 nm) are from water, clay minerals and organic matter [16,51]. The important spectra absorption features through the use of some data mining algorithms have been studied by Viscarra Rossel and Behrens [15] and Gholizadeh et al [17].…”
Section: Soil Spectral Reflectance Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that VIS-NIR-SWIR spectra contain useful information that can be used to derive estimates of soil properties. For example, absorption features in the VIS-NIR wavelength (400-1000 nm) are characteristics of the presence of soil carbon and iron oxide [34,35,[48][49][50], and those in the SWIR (1000-2500 nm) are from water, clay minerals and organic matter [16,51]. The important spectra absorption features through the use of some data mining algorithms have been studied by Viscarra Rossel and Behrens [15] and Gholizadeh et al [17].…”
Section: Soil Spectral Reflectance Patternmentioning
confidence: 99%
“…For example, Gholizadeh et al [14] indicated that the 1st derivative preprocessing method gave the best prediction of heavy metals in the Czech Republic mining areas, in comparison to 2nd derivative, multiplicative scatter correction (MSC), standard normal variate (SNV) and continuum removal (CR). Viscarra Rossel and Behrens [15] and Araujo et al [16] applied partial least square regression (PLSR), boosted regression trees (BRT) and support vector machine regression (SVMR) methods for the prediction of clay; SVMR offered the most successful prediction model due to its ability to solve the multivariate calibration problems and to reduce problems with heterogeneity and non-linearity. However, in a study by Gholizadeh et al [17], the memory based learning (MBL) technique outperformed PLSR, BRT and SVMR in soil texture prediction, which can be attributed to the selection of more appropriate neighbours to calibrate local models, as well as the inclusion of more suitable neighbours in each local model as a source of additional predictor variables [18].…”
Section: Introductionmentioning
confidence: 99%
“…2016, 8,341 3 of 17 been given to the prediction of other soil textural classes, including silt and sand. The use of VNIR/SWIR reflectance spectroscopy offers a lower precision than for clay, especially with particular chemometric algorithms.…”
Section: Study Areamentioning
confidence: 99%
“…The method makes multiple predictions that are based on resampling and weighting and belongs to the group of ensemble techniques [66]. It has the ability to take in a large number of weak relationships in a predictive model, and it is not sensitive to outliers in the calibration dataset [8]. Following Friedman [66], boosted models can be stated in the general form:…”
Section: Boosted Regression Treesmentioning
confidence: 99%
See 1 more Smart Citation